Effect of dilution on the growth of bacteria from blood cultures - Roome, A. P. C. H. (1968)
Artificial blood culture systems were set up to find the dilution with medium necessary to overcome the natural antibacterial effect of blood. The results indicate that blood should be diluted at least 1 in 50 in medium unless an additive such as Liquoid is used.